A study on energy properties of low excited states of deformed nuclei in rare-earth region - Turaeva, Gulyuz (Kulliyyah of Engineering, International Islamic University Malaysia, 2017)
The general properties of even-even rare earths nuclei are shown. The 62Sm, 64Gd, 66Dy, 70Yb, 72Hf and 74W nuclei are classified as deformed nuclei. Phenomenological models are used to understand the properties of deformed nuclei which account the Coriolis mixing of the experimentally known rotational bands. The inertial parameters for the even-even deformed nuclei are defined using the Harris parameterization. The energy and structure of wave function of low excited states are calculated. It has been found that a mixture of low excited bands should have a significant impact on the wave function of low-lying states of 0+n and 2+n bands. The theoretical values and experimental data of energy of ground and low excited states are comprised and analyzed for the 62Sm, 64Gd, 66Dy, 70Yb, 72Hf and 74W isotopes, correspondingly.